PENGARUH JENIS TRANSPORTASI TERHADAP KETERLAMBATAN KEHADIRAN MAHASISWA KE KAMPUS - Grasella Prescillia Pangaribuan; Darwis Robinson Manalu (STKIP Subang, 2026)
Students' punctual attendance at lectures is fundamental to the smooth conduct of academic activities; however, in reality, many students still arrive late, with the mode of transportation often cited as a contributing factor. This study aims to examine the influence of the chosen mode of transportation on the frequency of student lateness for lectures, determine its relationship with travel time to campus, and identify transportation-related obstacles that may trigger such lateness. The study employs an associative quantitative research design involving 120 active students selected via convenience sampling; data were collected online using a Google Forms questionnaire with a five-point Likert scale. Instrument validity was assessed using Pearson's product-moment correlation coefficient, while reliability was tested using Cronbach's alpha; both tests yielded valid and reliable results. Classical assumption testing—including Kolmogorov-Smirnov and Shapiro-Wilk normality tests and the Glejser test for heteroscedasticity—indicated that the regression model met the prerequisites for further analysis. Simple linear regression analysis yielded the equation Y = 12.958 − 0.145X. The t-test produced a significance value of 0.312 (> 0.05), as did the F-test (0.312 > 0.05), indicating that the mode of transportation does not have a significant influence on student lateness. The coefficient of determination (R²) was only 0.009, meaning that the mode of transportation accounts for only 0.9% of the variation in student tardiness, while the remaining 99.1% is influenced by factors outside the scope of this study, such as time management, personal discipline, travel distance, and traffic conditions.